Organ donation after death determination by circulatory criteria: Evaluation of two controversial practices - Honarmand, Kimia (My University, 2024)
Background Organ donation may occur after death determination by neurological criteria or by circulatory criteria (DCC). This thesis evaluates two controversial practices specific to DCC: (1) antemortem heparin administration to DCC donors with the aim of improving organ function, and (2) cardiac donation after DCC, which has not yet been adopted in Canada. Objectives (1) Describe antemortem heparin practices in DCC and explore its effects on transplant outcomes. (2) Describe the opinions, concerns, and insights of Canadian healthcare providers and the public regarding cardiac DCC. Methods Project 1: Systematic review and meta-regression analysis of published studies examining antemortem heparin in DCC donation. Projects 2 and 3: A qualitative interview study to evaluate the perspectives of healthcare providers and a mixed methods study involving focus groups with members of the Canadian public. Results Project 1: We found broad variability in the dosing and timing of heparin administration in DCC. While there were no clinical trials, meta-regression analysis detected no benefit to antemortem heparin in liver transplantation. Projects 2 and 3: Among healthcare providers, we found broad support for cardiac DCC but concerns about potential lack of support by the public. Among members of the public, we found majority support for cardiac DCC with priorities including respect for the wishes of dying individuals and ensuring that they are treated with dignity. Conclusions While preliminary results failed to demonstrate the benefit of antemortem heparin administration to DCC donors, high-quality clinical trials are needed to better evaluate the risks and benefits. Regarding cardiac DCC, despite healthcare providers’ concerns about lack of public support, most public stakeholders engaged in our study were supportive. The multi-modal approach of this thesis may serve as a model for evaluating other controversial practices in deceased organ donation.
Keywords: Organ Donation; Heart Transplantation